Austrian Syndrome in an Immunocompromised Patient—A Case Report - Arias-Morales, Carlos E.; Sharma, Shorabh; Flores-Chang, Marjorie M.; Rehmani, Razia; Koripalli, Venkata Sandeep; Dahdouh, Michelle (Frontiers in Medicine, 2020)
Austrian syndrome consists of a triad of endocarditis, meningitis and pneumonia caused by S. pneumoniae. With the arrival of many antibiotic therapies, the disease remains rare, however, it can be overlooked due to the lack of awareness. We present a case of Austrian syndrome in an immunocompromised patient complicated by multiorgan failure.